Psychological and psychophysiological differences between different sexual behaviors - Brody, Stuart (Akademie věd České republiky, 2012)
A dissertation abstract. The research focuses on psychological and psychophysiological differences between different sexual behaviors in women and men.
Keywords: sexuologie; interpersonální vztahy; sběr dat; Sexuality; Data Collection; sexuální chování; Sexual Behavior; sexualita; psychologie, klinická psychologie; Interpersonal Relations